"Planting the Seed": Perceived Benefits of and Strategies for Discussing Long‐Term Prognosis with Older Adults. Issue 12 (22nd October 2018) - Moré, Jayaji M.; Lang‐Brown, Sean; Romo, Rafael D.; Lee, Sei J.; Sudore, Rebecca; Smith, Alexander K.
Abstract : Objectives: To characterize the goals and approaches of clinicians with experience discussing long‐term prognostic information with older adults. Design: We used a semistructured interview guide containing 2 domains of perceived benefits and strategies to explore why and how clinicians choose to discuss long‐term prognosis, defined as life expectancy on the scale of years, with patients. Setting: Clinicians from home‐based primary care practices, community‐based clinics, and academic medical centers across San Francisco. Participants: Fourteen physicians, including 11 geriatricians and 1 geriatric nurse practitioner, with a mean age of 40 and a mean 9 years in practice. Measurements: Clinician responses were analyzed qualitatively using the constant comparisons approach. Results: Perceived benefits of discussing long‐term prognosis included establishing realistic expectations for patients, encouraging conversations about future planning, and promoting shared decision‐making through understanding of patient goals of care. Communication strategies included adapting discussions to individual patient preferences and engaging in multiple conversations over time. Clinicians preferred to communicate prognosis in words and with a visual aid, although most did not know of a suitable visual aid. Conclusion: Engaging in customized longitudinal discussions of long‐term prognosis aids clinicians in anchoring conversations about future planning and preparing patients for the end of life.J Am Geriatr Soc 66:2367–2371, 2018 .